EFEKTIVITAS PERATURAN BUPATI BREBES NOMOR 026 TAHUN 2015 TENTANG PEMBERDAYAAN MASYARAKAT DALAM PENURUNAN ANGKA KEMATIAN IBU DAN ANGKA KEMATIAN BAYI MELALUI MAKLUMAT DUKUN BAYI - Dwihatna Mustikarini Nugroho (MIH Unsoed, 2017)
This study aims to know and analyze the effectiveness of the regulation of the Regent of Brebes No. 026 the year 2015 and to know and analyze the factors that impede the implementation of the regulations of the Regent of Brebes No. 026 the year 2015.This research includes juridical sociological research categories. The data obtained are presented in narrative form. Based on the research results and discussion conclusion to be drawn as follows: first, Bupati of Brebes Regulations. No. 026 the year 2015 About community empowerment In Decreasing maternal mortality and infant mortality Through Baby Shaman Information seen from the theory of goal attainment, integration, adaptation is already effective in lowering maternal mortality in Brebes Regency. Second, barriers to the implementation of the regulations of the Regent of Brebes No. 026 the year 2015 About community empowerment In Decreasing maternal mortality and infant mortality Through Baby Shaman Information i.e. factor law because Regulation at the village level.Â Â Keywords: Effectiveness, Community Empowerment, Maternal and Child Mortality Rate